2006
DOI: 10.1111/j.1532-7795.2006.00498.x
|View full text |Cite
|
Sign up to set email alerts
|

Daily Variation in Adolescents' Sleep, Activities, and Psychological Well‐Being

Abstract: The daily diary method was used to examine the daily dynamics of adolescent sleep time, activities, and psychological well-being among an ethnically diverse sample of over 750 adolescents approximately 14-15 years of age. Studying and stressful demands during the day were modestly but consistently associated with less sleep that evening. Receiving less sleep at night, in turn, was modestly but consistently related to higher levels of anxiety, depressive feelings, and fatigue during the following day. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

32
225
2
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 253 publications
(261 citation statements)
references
References 25 publications
32
225
2
2
Order By: Relevance
“…In contrast, Crosby, LeBourgeois, and Harsh (2005) found that African American children (ages 2 to 8 years) had fewer hours of nighttime sleep but were more likely to nap than Caucasian children, resulting in similar total sleep hours. Fuligni and Hardway (2006) found Mexican adolescents reported more sleep on weekdays than those from European or Chinese backgrounds and found no racial/ethnic differences in weekend sleep hours or sleep variability. In the current study, we extended this past research by examining the extent to which racial/ethnic differences in sleep patterns are present in a nationally representative sample of both children and adolescents, and whether associations between race/ ethnicity and sleep are independent of the influence of family process, school schedule, and child activity variables.…”
mentioning
confidence: 79%
“…In contrast, Crosby, LeBourgeois, and Harsh (2005) found that African American children (ages 2 to 8 years) had fewer hours of nighttime sleep but were more likely to nap than Caucasian children, resulting in similar total sleep hours. Fuligni and Hardway (2006) found Mexican adolescents reported more sleep on weekdays than those from European or Chinese backgrounds and found no racial/ethnic differences in weekend sleep hours or sleep variability. In the current study, we extended this past research by examining the extent to which racial/ethnic differences in sleep patterns are present in a nationally representative sample of both children and adolescents, and whether associations between race/ ethnicity and sleep are independent of the influence of family process, school schedule, and child activity variables.…”
mentioning
confidence: 79%
“…Fuligni and Hardway (2006) found more time spent with friends each day to be associated with both average sleep duration and variability in sleep duration. Of note, positive peer relationships may have a positive effect on sleep functioning.…”
Section: Peer Factorsmentioning
confidence: 89%
“…Last, in a longitudinal, community-based study of 386 youth, childhood sleep problems predicted maternal ratings of internalizing problems in adolescence, with findings similar for boys and girls (Wong et al 2009 (Talbot et al 2010) as well as worsened mood and a decreased ability to regulate negative emotions (Baum et al 2014). In a daily diary study where adolescents reported on their sleep habits, daily activities (e.g., time spent studying, watching television), and mood each day over a 2-week period, Fuligni and Hardway (2006) found studying and stressful demands during the day to predict less sleep that evening, which in turn was associated with adolescents reporting higher levels of anxiety, depression, and fatigue the next day. Moreover, no evidence was found for daily ratings of anxiety and depression to impact that night's sleep (Fuligni and Hardway 2006), supporting the possibility that sleep has a negative impact on mood/anxiety more so than the reverse.…”
Section: Mental Healthmentioning
confidence: 93%
See 2 more Smart Citations